2017
DOI: 10.3892/ijo.2017.4041
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin inhibits angiogenesis by blocking Gas6/Axl signaling pathway

Abstract: Growth arrest-specific protein 6 (Gas6) induces the activation of Axl receptor tyrosine kinase (Axl), which plays an important role in angiogenic processes, including proliferation, migration, invasion, tube formation and pericyte recruitment of endothelial cells. The inhibition of Gas6/Axl pathway has been demonstrated to be an effective anti-angiogenic therapy. Luteolin, which is a natural active flavonoid, has been reported to possess anti-angiogenic effects. However, the underlying mechanism of luteolin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 38 publications
1
12
0
1
Order By: Relevance
“…The parameters measured in this assay via the Angiogenesis Analyser plugin [ 40 ]; the number (nb) of junctions and meshes, number and length of master segments and segments offer high sensitivity in the detection of different features of angiogenesis [ 41 ]. As shown in Figure 2 , the reference standard luteolin showed around 30% decrease in tube formation, in agreement with previous reports [ 38 , 42 ]. In this regard, all of the evaluated derivatives demonstrated higher inhibition of tube formation than the active reference luteolin ( Figure 2 ).…”
Section: Resultssupporting
confidence: 92%
“…The parameters measured in this assay via the Angiogenesis Analyser plugin [ 40 ]; the number (nb) of junctions and meshes, number and length of master segments and segments offer high sensitivity in the detection of different features of angiogenesis [ 41 ]. As shown in Figure 2 , the reference standard luteolin showed around 30% decrease in tube formation, in agreement with previous reports [ 38 , 42 ]. In this regard, all of the evaluated derivatives demonstrated higher inhibition of tube formation than the active reference luteolin ( Figure 2 ).…”
Section: Resultssupporting
confidence: 92%
“…The second and third sets, however, tested the antiangiogenic activity of flavonoids on CAMs with abnormal angiogenesis using either proangiogenic factors for set 2 (4 studies) or cancer cell lines for set 3 (9 studies). 10 studies [ 18 , 95 , 100 , 132 , 137 , 139 , 140 , 141 , 145 , 149 ] out of the 25 eligible studies were not included in any of the conducted meta-analyses as they failed to report the required data outcomes or did not fit under any particular subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…AXL is expressed mainly in the vascular endothelium, and is involved in the regulation of proliferation, migration, invasion, and the formation of endothelial cells (Li et al, 2017). It was shown that Gas6/UFO signaling plays an important role in the survival of endothelial cells during the development of acidosis (Gustafsson et al, 2009).…”
Section: Discussionmentioning
confidence: 99%